The Engagement of the Kerala Jewish Community in Land and Agrarian Networks: The Witness of the Palm-Leaf Documents - Thomas, Susan (Entangled Religions, 2020)
This article tries to understand the multiple engagements of the Jewish community in land and agrarian networks in the nineteenth century through the palm leave records (grantavari) that have been unearthed from both Jewish and non-Jewish sources. Even though the article deals with the economic networks and acquisition of land in Kochi and Travancore, the argument is that the beginning of these changes can be attributed to internal factors in the dynamics of trade and mercantile circulation of Kerala in the prior centuries. This can be inferred from the grantavari-s of temples, ruling and land owning houses from the region. The image of the ‘Black’ Jews as economically backward and servile to the ‘White’ Jews is questioned. The similarity of the governing structures in the church and the synagogue is explored. These palm leaves give us a glimpse of how the divide within the Jewish community on the basis of race and purity was internalised by the other communities who started thinking of their difference in terms of colour and in their document identified them as either ‘White’ or ‘Black’ Jews.